2021
DOI: 10.1093/nargab/lqab024
|View full text |Cite
|
Sign up to set email alerts
|

CladeOScope: functional interactions through the prism of clade-wise co-evolution

Abstract: Mapping co-evolved genes via phylogenetic profiling (PP) is a powerful approach to uncover functional interactions between genes and to associate them with pathways. Despite many successful endeavors, the understanding of co-evolutionary signals in eukaryotes remains partial. Our hypothesis is that ‘Clades’, branches of the tree of life (e.g. primates and mammals), encompass signals that cannot be detected by PP using all eukaryotes. As such, integrating information from different clades should reveal local co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 47 publications
3
24
0
Order By: Relevance
“…Recent investigations on functional potential prediction of bacteria by employing PICRUSt2 in different environments, including soils (Toole et al, 2021), seawater (Xue et al, 2021), marine sediment (Su et al, 2018) are in help to decipher the detailed function variations successfully. In addition, benefiting from the function prediction of bacteria from the 16S rRNA gene sequences solely, diverse unknown microbes could be identified phylogenetically (Tsaban et al, 2021). With the unique contribution of each clade to Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways are developed, PICRUSt2 prediction is increasingly applied in microbial ecology studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations on functional potential prediction of bacteria by employing PICRUSt2 in different environments, including soils (Toole et al, 2021), seawater (Xue et al, 2021), marine sediment (Su et al, 2018) are in help to decipher the detailed function variations successfully. In addition, benefiting from the function prediction of bacteria from the 16S rRNA gene sequences solely, diverse unknown microbes could be identified phylogenetically (Tsaban et al, 2021). With the unique contribution of each clade to Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways are developed, PICRUSt2 prediction is increasingly applied in microbial ecology studies.…”
Section: Introductionmentioning
confidence: 99%
“…genes that are either conserved or lost as a group) are functionally related, often belonging to the same pathway ( Sherill-Rofe et al, 2019 ; Tabach et al, 2013a ; Tabach et al, 2013b ; Schwartz et al, 2013 ). We have shown that both across-clade and within-clade measures of co-evolution can be informative, and thus we computed NPPs both across all eukaryotes ( Figure 1A and Figure 1—figure supplement 1A ) and within mammals ( Figure 1B and Figure 1—figure supplement 1B ) as described previously ( Sherill-Rofe et al, 2019 ; Bloch et al, 2020 ; Tsaban et al, 2021 ; Braun et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…We used the pipeline we described in Tsaban et al, 2021 to calculate the Normalized Phylogenetic Profile (NPP) of 1028 eukaryotic species and rank genes based on their evolutionary similarity to MECP2. Briefly, 20,192 human proteins (one representative protein sequence per gene) were downloaded from UniProt reference proteomes (June 2018 release) ( Bateman and UniProt Consortium, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic profiling is one such analysis method. In this method, when two ortholog groups (OGs) have similar occurrence patterns among species in a table of OGs, the two OGs are presumed to be functionally related ( Kensche et al , 2008 ; Moi et al , 2020 ; Niu et al , 2017 ; Pellegrini et al , 1999 ; Stupp et al , 2021 ; Tremblay et al , 2021 ; Tsaban et al , 2021 ). Although phylogenetic profiling was first proposed to detect protein–protein interactions, this method in principle captures any functional relationships between genes.…”
Section: Introductionmentioning
confidence: 99%